RE-EVALUATING MACHINE CONSCIOUSNESS THROUGH SUFI EPISTEMOLOGY: ETHICAL AND ONTOLOGICAL IMPLICATIONS FOR THE DEVELOPMENT OF ARTIFICIAL INTELLIGENCE - Hakim, Faisol; Zaini, Akhmad (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
The rapid advancement of Artificial Intelligence (AI) has sparked extensive discourse on machine consciousness, typically framed within neurocognitive and representational paradigms. However, such approaches often neglect the ontological and spiritual dimensions of consciousness. This study aims to reassess the concept of machine consciousness through the lens of Sufi epistemology, focusing on ma‘rifah as the core of human spiritual awareness. Employing a Systematic Literature Review(SLR) based on the PRISMA framework, 35 articles published between 2013 and 2025 were thematically analyzed using the Watase application. The findings reveal a predominance of reductionist perspectives that equate consciousness with algorithmicprocesses, while disregarding metaphysical aspects and transcendental values. From the Sufi perspective, consciousness is viewed as an emanation of the soul (ruh), not merely a product of cognition. Sufi ethical values such as tawakkul, ikhlas, and ihsan are proposed as an alternative ethical framework in AI development to ensure alignment with human dignity and spirituality. This study concludes that AI may simulate consciousness but cannot possess true conscious existence. It recommends the integration of Sufi values into a value-aligned AI framework as a pathway toward a dignified and transcendental digital civilization.